الإلتفات بالضمير في شعر أبي تمام الطائي (ت 231 هــ): دراسة بلاغية في قصيدتين من مدائحه - العاني، ماجد محمد جاسم (جامعة تكريت - كلية الآداب, 2018)
يعد الالتفات مؤشر دلالي بارز اختصت به العربية دون غيرها من اللغات وذلك لما يحدثه من تغيير في السلوك التركيبي المتداول في بناء النص أو الجملة إلى مستوى تركيبي آخر لفائدة معنوية اقتضتها دلالة السياق الجديد، وهو في اللغة مأخوذ من التفات الإنسان عن يمينه وشماله وفي الاصطلاح هو الانتقال من أسلوب إلى أسلوب آخر ولا يكون هذا الانتقال إلا إذا اقتضى الحال ذلك وأريد به نوع من الإبداع والمتعة الفنية وله ثلاثة أقسام رئيسة هي: (الالتفات بالضمائر، الالتفات العددي، والالتفات الزمني) ويأتي كل قسم منها بعدة صور وله فوائد عامة وخاصة أما الفوائد العامة فهي تطرية الكلام وصيانة السمع من الضجر والملال لما جبلت عليه النفوس من حب التنقلات والسآمة من الاستمرار على منوال واحد، أما الفوائد الخاصة فتختلف بخواص مجالاتها وهي بحسب الأغراض منها للتعميم والتنبيه والتتميم والمبالغة والاختصاص والاهتمام والتوبيخ ومعلوم ما لأبي تمام من مكانة مرموقة في الشعر العربي، وقد أحسن وأجاد في استعمال هذا الأسلوب في مدائحه فاستعمل الالتفات بالضمير في القصيدة الأولى في مدح أبي دلف العجلي للتعبير عن البعد عن المكروه والقرب من المحبوب أولا ولتوسعة المعنى وتحسينه ثانيا أما قصيدته الثانية في مدح أبي الحسين بن شبابه فقد روح في استعمال هذا الأسلوب بين ضمير الغائب وضمير الخطاب ثم ضمير الغائب ثانية وذلك تبعا للعلاقة بين النظرية والتطبيق والخلق والسلوك لتحويل سلوك ممدوحه وأفعاله إلى صفات ثابتة ونظريات خلقية مقصورة عليه فيكون سلوكه الصورة العملية المثلى للقيمة الخلقية.
The attention is a sign of the significance of the distinctive Arabic specialized in other languages, because of the change in the behavior of the structural rolling in the construction of the text or sentence to another level of moral benefit required by the significance of the new context, which is in the language taken from the human turn to his right and north and the term is The transition from style to style is not a transition, but if necessary, and I want a kind of creativity and artistic pleasure and has three main sections are (attention to conscience, numerical attention, and time) and each section comes in several pictures and has general benefits, especially the benefits General is an evolutionary Speech and hearing maintenance from the boredom and boredom of the souls of the souls of the movements of the movement and accuse of the continuation of the same pattern, but the special benefits vary with the characteristics of the areas, which according to the purposes of generalization and warning and completion and exaggeration and specialization and attention and reprimand and knowledge of my father is a prestigious position in Arabic poetry has been better and worse in The use of this method in his praise used to pay attention to the conscience in the first poem in the praise of Abi Dlaf Alqali to express the distance from the abomination and proximity to the beloved first and to expand the meaning and improve the second poem second in the praise of Abu Hussein bin Shabab, This method between the conscience of the absent and the consciences of the discourse and then the conscience of the absent again, depending on the relationship between theory and practice, behavior and behavior to transform the behavior of the prodigal and to the fixed qualities and theories are limited to the behavior of the image is the optimal process of moral value.
Keywords: الشعر العربي -- الشعراء العرب -- الدواوين والقصائد -- الدراسات البلاغية -- أبي تمام الطائي